New Model of Organization of Logistics Processes in Warehouse and Effect of Logistics Costs Reduction - Kučera, Tomáš (Wydawnictwo Politechniki Częstochowskiej, 2018)
The topic of logistics costs and their solution through innovative management methods has recently become very actual. The article is based on information that is drawn from the Scopus and Web of Science databases and from the internal data of the logistics service provider and the production company. The article focuses on the issue of processing calculations, taking into account all the costs associated with the logistics activity of the production company. It also deals with the possible application of management synergy effect between a logistics service provider and a production company. The aim of the article is to include in the case study, which is one of qualitative scientific method, the proposal to integrate a logistic service provider not only into the logistic manipulation and warehousing but to involve this provider in a pre-production operations of heating and air-conditioning bonding, including sequential delivery to the production line thereby creating synergies throughout the logistics chain. The resulting innovative solution in the case study should be higher productivity and lower costs for the final product.
Nový model organizace logistických procesů ve skladu a efekt redukce logistických nákladů
Keywords: calculation of logistics costs; logistics service provider; synergy effect; warehousing costs; kalkulace logistických nákladů; poskytovatel logistických služeb; synergický efekt; náklady na skladování